Improved grass fibrous root algorithm for exergy optimization of a high-temperature PEMFC - Xiaohui Lu; Jianglin Ren; Lin Guo; Peifang Wang; Nasser Yousefi (Energy Reports, 2020)
This paper presents an exergy assessment for a proposed power generation system that is used the organic Rankine cycle to recycle the waste heat from a high-temperature proton exchange membrane fuel cell (HT-PEMFC). To do so, mathematical model for the studied PEMFC along with the water management system have been introduced. Parametric analysis has been directed to study the impact of different economic and thermodynamic parameters, like the fuel cell irreversibility, exergy efficiency, and its work. For optimal designing the PEMFC, its parameters have been optimized by considering three objective functions, i.e. irreversibility, exergy efficiency, and its work. The optimization process has been performed based on a new model of fibrous root optimization algorithm improved. Simulation results of the presented algorithm have been compared with empirical results, genetic algorithm, and the basic of fibrous root optimization algorithm. The optimized values of irreversibility, exergy efficiency, work for the proposed algorithm are achieved 0.012, -0.439, and -0.4993, respectively which has the best values compared with the other analyzed algorithms.
Keywords: 330; Improved; Exergy analysis; Proton exchange membrane fuel cell; Grass fibrous root algorithm; Irreversibility